African Swine Fever Virus Ubiquitin-Conjugating Enzyme Interacts With Host Translation Machinery to Regulate the Host Protein Synthesis - Barrado-Gil, Lucía; Del Puerto, Ana; Muñoz-Moreno, Raquel; Galindo, Inmaculada; Cuesta-Geijo, Miguel Ángel; Urquiza, Jesús; Nistal-Villán, Estanislao; Maluquer de Motes, Carlos; Alonso, Covadonga (Frontiers in Microbiology, 2020)
African Swine Fever virus (ASFV) causes one of the most relevant emerging diseases affecting swine, now extended through three continents. The virus has a large coding capacity to deploy an arsenal of molecules antagonizing the host functions. In the present work, we have studied the only known E2 viral-conjugating enzyme, UBCv1 that is encoded by the I215L gene of ASFV. UBCv1 was expressed as an early expression protein that accumulates throughout the course of infection. This versatile protein, bound several types of polyubiquitin chains and its catalytic domain was required for enzymatic activity. High throughput mass spectrometry analysis in combination with a screening of an alveolar macrophage library was used to identify and characterize novel UBCv1-host interactors. The analysis revealed interaction with the 40S ribosomal protein RPS23, the cap-dependent translation machinery initiation factor eIF4E, and the E3 ubiquitin ligase Cullin 4B. Our data show that during ASFV infection, UBCv1 was able to bind to eIF4E, independent from the cap-dependent complex. Our results provide novel insights into the function of the viral UBCv1 in hijacking cellular components that impact the mTORC signaling pathway, the regulation of the host translation machinery, and the cellular protein expression during the ASFV lifecycle.